Substantial Variability of Multiple Microbial Communities Collected at Similar Acidic Mine Water Outlets - Falteisek, Lukáš; Duchoslav, Vojtěch; Čepička, Ivan (Microbial ecology, 2016)
Deep sequencing of prokaryotic 16S rDNA regularly reveals thousands of microbial species thriving in many common habitats. It is still unknown how this huge microbial diversity, including many potentially competing organisms, may persist at a single site. One of plausible hypotheses is that a large number of spatially separated microcommunities exist within each complex habitat. Smaller subset of the species may exist in each microcommunity and actually interact with each other. We sampled two groups of microbial stalactites growing at a single acidic mine drainage outlet as a model of multiplicated, low-complexity microhabitat. Samples from six other sites were added for comparison. Both tRFLP and 16S rDNA pyrosequencing showed that microbial communities containing 6 to 51 species-level operational taxonomic units (OTU) inhabited all stalactites. Interestingly, most OTUs including the highly abundant ones unpredictably alternated regardless of physical and environmental distance of the stalactites. As a result, the communities clustered independently on sample site and other variables when using both phylogenetic dissimilarity and OTU abundance metrics. Interestingly, artificial communities generated by pooling the biota of several adjacent stalactites together clustered by the locality more strongly than when the stalactites were analyzed separately. The most probable interpretation is that each stalactite contains likely random selection from the pool of plausible species. Such degree of stochasticity in assembly of extremophilic microbial communities is significantly greater than commonly proposed and requires caution when interpreting microbial diversity.
Keywords: Neutral processes; biodiverzita; hornictví; Acidophiles; DNA bakterií; druhová specificita; RNA, Ribosomal, 16S; DNA, Bacterial; shluková analýza; Mining; Species Specificity; Community assembly; voda; Phylogeny; Phylogenetic dissimilarity; Water; kyseliny; Bacteria; Biodiversity; Sequence Analysis, DNA; Water Microbiology; Chemolithotrophy; biofilmy; sekvenční analýza DNA; mikrobiologie vody; Cluster Analysis; fylogeneze; Biofilms; RNA ribozomální 16S; Acids